Expanding social security in Indonesia: The processes and challenges - Asep Yadi Suryahadi; Vita Febriany; Athia Yumna (United Nations Research Institute for Social Development (UNRISD), 2014)
This paper reviews the development of social security provision in Indonesia, which has evolved from very little in its early years to the privilege of formal sector workers during the New Order period to universal coverage, at least in principle, in the current period. These changes were in line with and driven by the developments of the Indonesian economy in general, which has gone through various episodes marked by both booms and crises. There are two important milestones in the development of social security in Indonesia. First, after the change in government during the chaotic mid-1960s, the New Order government gradually developed various social security schemes, but limited to formal sector workers only. Second, after the Asian Financial Crisis at the end of 1990s exposed the weaknesses of the social security system in place, successive governments established a stronger social security system by adopting universal coverage. The challenges for implementing it, however, are formidable due to Indonesias vast geography, huge population and diverse availability and quality of infrastructure.
Keywords: 330